2019
DOI: 10.3390/molecules24203632
|View full text |Cite
|
Sign up to set email alerts
|

A Polysaccharide Isolated from Codonopsis pilosula with Immunomodulation Effects Both In Vitro and In Vivo

Abstract: In this study, an acidic polysaccharide from Codonopsis pilosula Nannf. var. modesta (Nannf.) L. T. Shen (WCP-I) and its main fragment, WCP-Ia, obtained after pectinase digestion, were structurally elucidated and found to consist of a rhamnogalacturonan I (RG-I) region containing both arabinogalactan type I (AG-I) and type II (AG-II) as sidechains. They both expressed immunomodulating activity against Peyer’s patch cells. Endo-1,4-β-galactanase degradation gave a decrease of interleukine 6 (IL-6) production co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The results in our research found that the relative mRNA expression level of IL-4 and IL-10 in PAMK+CTX group was significant decrease when compared with CTX group, which indicated that PAMK could alleviate the imbalance of cytokines caused by CTX and maintain the balance of cytokines secretion levels. Similar to our research, Zhu and Zhou found that Codonopsis pilosulaA Polysaccharide and Lycium barbarum polysaccharide could increase the serum secretion level of TGF-β, IL-6, TNF-α, sIgA, enhance intestinal flora, increase CD4/CD8 T lymphocytes ratio to enhance the body immunity level( Zou et al., 2019 ; Zhu et al., 2020 ) Ying and zhou indicated that polysaccharide could alleviate the immunosuppression induced by CTX through increase the serum secretion level of IL-2, IL-3, IL-6, TGF-β( Wang et al., 2018 ; Ying et al., 2020 ). Taken together, these findings confirm that PAMK can alleviate the imbalance level of cytokines induced by CTX.…”
Section: Discussionsupporting
confidence: 83%
“…The results in our research found that the relative mRNA expression level of IL-4 and IL-10 in PAMK+CTX group was significant decrease when compared with CTX group, which indicated that PAMK could alleviate the imbalance of cytokines caused by CTX and maintain the balance of cytokines secretion levels. Similar to our research, Zhu and Zhou found that Codonopsis pilosulaA Polysaccharide and Lycium barbarum polysaccharide could increase the serum secretion level of TGF-β, IL-6, TNF-α, sIgA, enhance intestinal flora, increase CD4/CD8 T lymphocytes ratio to enhance the body immunity level( Zou et al., 2019 ; Zhu et al., 2020 ) Ying and zhou indicated that polysaccharide could alleviate the immunosuppression induced by CTX through increase the serum secretion level of IL-2, IL-3, IL-6, TGF-β( Wang et al., 2018 ; Ying et al., 2020 ). Taken together, these findings confirm that PAMK can alleviate the imbalance level of cytokines induced by CTX.…”
Section: Discussionsupporting
confidence: 83%
“…These herbs and chemical constituents of GXV have been reported to be beneficial to CAD. Codonopsis Radix shares immunomodulation effects [68,69]. Radix Codonopsis polysaccharide, an active compound in Codonopsis Radix, could maintain the T-cell balance against hydrocortisone disturbance [70].…”
Section: Discussionmentioning
confidence: 99%
“…As a canonical and well-known Chinese medicine formula, SLBZ-AP is first described in " e Prescriptions of the Bureau of Taiping People's Welfare Pharmacy" in Song-dynasty [19] and contains twenty-eight species of TCM as Dangshen, Fuling, Baizhu, Gancao, and so on . ere are chemical components as saccharides (Dang Shen, Fu Ling, Bai Bian Dou) [37,38], glycosides (Shan Yao, Jie Geng, Shan Zhu Yu, Bai Shao) [39][40][41][42], and flavonoids (Bai Zhu, Gan Cao) [43,44] mainly in SLBZ-AP. Saccharides have immunomodulation effects [37].…”
Section: Discussionmentioning
confidence: 99%
“…ere are chemical components as saccharides (Dang Shen, Fu Ling, Bai Bian Dou) [37,38], glycosides (Shan Yao, Jie Geng, Shan Zhu Yu, Bai Shao) [39][40][41][42], and flavonoids (Bai Zhu, Gan Cao) [43,44] mainly in SLBZ-AP. Saccharides have immunomodulation effects [37]. Glycosides as saponins [39] and flavonoids [44] have anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%